Impact of Long COVID on Lung Function in Children - Zeynep Reyhan ONAY; Sinem CAN OKSAY; Deniz MAVI TORTOP; Gulay BILGIN; Yetkin AYHAN; Ferit DURANKUS; Saniye GIRIT (Medeniyet Medical Journal)
Objective: While the coronavirus disease-2019 (COVID-19) pandemic has generally resulted in milder illness among children than adults, persistent respiratory symptoms have been increasingly reported in this population. Methods: We conducted a prospective, single-center cohort study focusing on children experiencing prolonged respiratory symptoms after contracting COVID-19. Spirometry, 6- minute walk tests (6MWTs), and tests of lung volume, the diffusing capacity of the lungs for carbon monoxide (DLCO), and fractional exhaled nitric oxide (FeNO) were performed on COVID-19 survivors at least 4 weeks after infection and a group of healthy control subjects. Results: Fifty-five children with long-term COVID and 55 healthy control subjects were recruited. The weight, height, and body mass index Z-scores were similar in the groups. Within a median duration of 85 days (minimum-maximum: 35-194) following COVID-19 infection, a restrictive pattern was observed to be more common in the study group (p=0.021). In children with long COVID, 6MWT distances, DLCO Z-scores, and the predicted values of spirometry and lung volume tests were found to be significantly lower but in the normal range. The average predicted values for DLCO, FeNO, and 6MWT were similar in the two groups. Conclusions: Prolonged respiratory symptoms often persist long after COVID-19 infection, necessitating comprehensive evaluation of affected children. Close monitoring, including spirometry and lung volume assessments, is crucial for children with abnormalities in lung imaging. However, FeNO measurements were found to be ineffective in monitoring long COVID.